Risk factors for neonatal death in the capital city with the lowest infant mortality rate in Brazil - Leandro Pereira Garcia; Camila Mariano Fernandes; Jefferson Traebert (Brazilian Society of Pediatrics, 2019)
Objectives: To analyze the risk factors for neonatal death in Florianópolis, the Brazilian city capital with the lowest infant mortality rate. Method: Data were extracted from a historical cohort with 15,879 live births. A model was used that included socioeconomic, behavioral, and health service use risk factors, as well as the Apgar score and biological factors. Risk factors were analyzed by hierarchical logistic regression. Results: Based on the multivariate analysis, socioeconomic factors showed no association with death. Insufficient prenatal consultations showed an OR of 3.25 (95% CI: 1.70-6.48) for death. Low birth weight (OR 8.42; 95% CI: 3.45-21.93); prematurity (OR 5.40; 95% CI: 2.22-13.88); malformations (OR 4.42; 95% CI: 1.37-12.43); and low Apgar score at the first (OR 6.65; 95% CI: 3.36-12.94) and at the fifth (OR 19.78; 95% CI: 9.12-44.50) minutes, were associated with death. Conclusion: Differing from other studies, socioeconomic conditions were not associated with neonatal death. Insufficient prenatal consultations, low Apgar score, prematurity, low birth weight, and malformations showed an association, reinforcing the importance of prenatal access universalization and its integration with medium and high‐complexity neonatal care services. Resumo: Objetivos: Analisar os fatores de risco para o óbito neonatal em Florianópolis, capital brasileira com a menor taxa de mortalidade infantil. Método: Os dados foram extraídos de coorte histórica, contando com 15.879 nascidos vivos. Utilizou‐se modelo ordenando fatores de risco socioeconômicos, comportamentais e de utilização dos serviços de saúde, além do escore de Apgar e de fatores biológicos. Os fatores de risco foram analisados por regressão logística hierarquizada. Resultados: Com base na análise multivariada, os fatores socioeconômicos não mostraram associação com o óbito. Consultas pré‐natais insuficientes apresentaram um OR 3,25 (IC95% 1,70-6,48) para óbito. Baixo peso ao nascer (OR 8,42; IC95% 3,45-21,93); prematuridade (OR 5,40; IC95% 2,22-13,88); malformações (OR 4,42; IC95% 1,37-12,43); baixo escore de Apgar no 1o (OR 6,65; IC95% 3,36‐12,94) e no 5o (OR 19,78; IC95% 9,12-44,50) minutos associaram‐se ao óbito. Conclusão: Diferente de outros estudos, as condições socioeconômicas não se associaram ao óbito neonatal. Pré‐natal insuficiente, baixo escore de Apgar, prematuridade, baixo peso e malformações mostraram associação, reforçando a importância da universalização do acesso ao pré‐natal e da integração deste com serviços de atenção ao recém‐nascido, de média e alta complexidade. Keywords: Mortality, Newborn, Risk factors, Palavras‐chave: Mortalidade, Recém‐nascido, Fatores de risco